Spasmofilia - Iswandi Erwin; Aida Fithrie (PT. Kalbe Farma Tbk., 2017)
Spasmofilia didefinisikan sebagai keadaan patologis peninggian iritabilitas saraf dan otot disebabkan gangguan keseimbangan elektrolit, terutama ion Kalsium (Ca++) dan ion Magnesium (Mg++). Spasmofilia juga dikenal dengan nama lain, tetani laten, tetani kriptogenik, sindrom tetani dan / atau sindrom hiperventilasi. Seorang pria 33 tahun dengan kram sejak 3 bulan disertai nyeri kepala terutama saat lelah dan letih. Nyeri pada seluruh kepala, terasa mengikat tidak berdenyut, Dijumpai tender points pada kedua sisi bahu dan leher. Tanda Chvostek I dan II +/+, tanda iskemik Trousseau (+). Didapatkan hipokalsemia pada pemeriksaan laboratorik dan multiplets pada tes iskemik dan hiperventilasi elektromiografi jarum pada m. interossei dorsalis I.Spasmophilia is defined as pathological condition of end-nerve and muscle irritability caused by electrolyte imbalance, mainly calcium and magnesium ion. It is also known as latent –cryptogenic tetany and / or hyperventilation syndrome. A 33 year-old male with spasm and headache since 3 months. Muscle spasm occurred involuntary all over the body, especially both upper limbs and hands. Headache is felt all over the head, strangling but not pulsating, without nausea nor vomiting, not exacerbated by physical activity, cough or Valsava. Tender points found in both shoulders and neck. Chvostek I and II signs, Trousseau ischemic sign.were positive. Hypocalcemia was found on laboratory examination. Ischemic test and hyperventilation in needle electromyography on first dorsal interossei muscle produced multiplets.